Biology-Critical Thinking Skills of High School Students in Terms of Gender and School Location - Suci Hatru Ramadhani*; Puguh Karyanto; Bowo Sugiharto (Universitas Syiah Kuala, 2023)
Students' critical thinking skills (CTS) in Indonesia are still relatively low. This study describes students' and the relationship between CTS and their gender and school location. The research was conducted using a cross-sectional survey method. The sampling technique was convenience sampling involving 91 men and 134 women from 7 public high schools in Bener Meriah district which are located in rural areas and 4 are located in urban areas. Students' CTS were measured using essay tests collected via google form and the results were analyzed descriptively. Furthermore, a correlation test was carried out between gender and students' school location on CTS with the Pearson correlation in the SPSS 25 program. The results showed that the value of students' CTS who attended urban areas had an average score of 48.6, while those who attended rural areas of 36.6. The average score of the boys was 39.4, while the average score of the girls was 50.3. The relationship between gender and CTS shows a value of 0.217, while the relationship between school location and CTS shows a value of -0.117. It was concluded that students who attend schools in urban areas have superior CTS compared to those in rural areas and female students are superior to male students. The relationship between school location and gender on students' CTS is low